Competitive advantage in chemical business: the case study of Clariant (M) Sdn Bhd / Mohd Shaharuddin Abdul Ghani and Latiff Muhamad - Abdul Ghani, Mohd Shaharuddin; Muhamad, Muhamad (2015)
The aim of this study is to examine the relationship between competitive priorities and the competitive advantage of local specialty chemical business in Malaysia. A Case study of Clariant (Malaysia) Sdn. Bhd.(CMSB) has been carried out to determine the element of competitive priorities that affect its competitive advantages which contribute in achieving its company objective to become a market leader in delivery of specialty chemical supply with associated service. Situational analysis such as PESTEL analysis and Porter’s five forces were utilized to support the surveyed data analysis. This study will be utilizing the SWOT analysis by identifying external and internal factors that direct to the formulation of the Clariant’s strategies. These tools wiii assist CMSB to identify its strategy to achieved competitive advantage in the turbulent environment of specialty chemicals industry. CMSB’s competitive priorities elements have been analyzed on its current business and the importance of quality, cost, flexibility and delivery that affect competitive advantage were then identified. The competitive priorities were analyzed for its roles of important to the effect of competitive advantage which will help CMSB to develop its own competencies and strategies. The study found that the element of quality was the most important competitive priorities that effect CMSB’s competitive advantage. Based on the findings of this study, it is strongly recommended that CMSB’s management to focus on maintaining the element of quality in order to be resilient in terms of its competitive advantage. The outcomes of the study were used to formulate CMSB strategies in order to achieve it competitive advantage.